Spine technology handbook - Kurtz, Steven M., 1968- (Elsevier Academic Press, 2006)
Over the past decade, there has been rapid growth in bioengineering applications in the field of spine implants. This book explains the technical foundation for understanding and expanding the field of spine implants, reviews the major established technologies related to spine implants, and provides reference material for developing and commercializing new spine implants. The editors, who have a track record of collaboration and editing technical books, provide a unified approach to this topic in the most comprehensive and useful book to date. Related website provides the latest information on spine technology including articles and research papers on the latest technology and development. Major technologies reviewed include devices used for fusion (screws, plates, rods, and cages), disc repair and augmentation, total disc replacement, and vertebral body repair and augmentation. Technology landscape, review of published/public domain data currently available, and safety and efficacy of technology discussed in detail.